Da formação polivalente ao movimento da educação matemática : uma trajetória histórica da formação de professores de Matemática na Universidade Federal de Rondônia em Ji-Paraná (1988-2012) - Albuquerque, Marlos Gomes de (2014)
The aim of this thesis was to do an investigative historical study at the Federal University of Rondônia, about the history of antique Short Major in Science with Specialization in Mathematics Course, passing over his creation, the consolidation’s process until the current Major Course in Math in the Ji-Paraná’s Campus, identifying the permanency and ruptures that became in inflexion’s points during the history of the course. The study was developed from a perspective that values the relationship between the global and local history by reading about the way that the movement of Mathematics Education happened, how it was taking place in the course, as new curricular changes were implemented in the pedagogical project of this degree. Sustained methodologically in the History of Mathematics Education, we seek evidence to build the historical sources for the construction of the present study’s support through interviews with teachers, former teachers and students of the first undergraduate classes; official documents (educational legislation, minutes, resolutions, course’s projects, conventions, statutes, regulations); photographic images and journalistic reports. The theoretical and methodological reference were built based upon the writings of Marc Bloch, Jacques Le Goff and Roger Chartier, all linked to the current historiography from the Annales School. For the analysis, we performed a careful reading of the documents and built “a triangle” out from the latter with the eyewitnesses’ accounts all together with our over-twodecades experience as teachers of this course, from which was possible to identify continuities and also ruptures that were formed or established over the time. It was evident, given the results, that yet the course was constituted with a faculty that has come from different Brazil’s regions and which has also come from a multipurpose training in science to a more contentful training in mathematics. However, with the creation of the Week of Mathematics, the SBEM’s institutionalization through Rondonia’s regional delegation and the Teacher Educators’ post-graduate’s training stricto sensu, the course took a strong inclination towards Mathematics.